Photosensitization of nanoparticulate TiO2 using a Re(I)-polypyridyl complex: studies on interfacial electron transfer in the ultrafast time domain - Kar, Prasenjit; Banerjee, Tanmay; Verma, Sandeep; Sen, Anik; Das, Amitava; Ganguly, Bishwajit; Ghosh, Hirendra N. (Physical Chemistry Chemical Physics, 2012)
We have synthesized a new photoactive rhenium(I)-complex having a pendant catechol functionality [Re(CO)3Cl(L)] (1) (L is 4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol) for studying the dynamics of the interfacial electron transfer between nanoparticulate TiO2 and the photoexcited states of this Re(I)-complex using femtosecond transient absorption spectroscopy. Our steady state absorption studies revealed that complex 1 can bind strongly to TiO2 surfaces through the catechol functionality with the formation of a charge transfer (CT) complex, which has been confirmed by the appearance of a new red-shifted CT band. The longer wavelength absorption band for 1, bound to TiO2 through the proposed catecholate functionality, could also be explained based on the DFT calculations. Dynamics of the interfacial electron transfer between 1 and TiO2 nanoparticles was investigated by studying kinetics at various wavelengths in the visible and near infrared regions. Electron injection into the conduction band of the nanoparticulate TiO2 was confirmed by detection of the conduction band electron in TiO2 (Image ID:c2cp24105f-t1.gif) and the cation radical of the adsorbed dye (1˙+) in real time as monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (<100 fs) electron injection was observed. Back electron transfer dynamics was determined by monitoring the decay kinetics of 1˙+ and Image ID:c2cp24105f-t2.gif.

Proton-coupled electron transfer in a hydrogen-bonded charge transfer complex - Verma, Sandeep; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry B, 2016)
A proton-coupled electron transfer (PCET) reaction in a hydrogen bonded charge-transfer (CT) complex of 4-([2,2'-bipyridin]-4-yl)phenol (bpy-phenol) with a F- ion has been investigated by ultrafast time-resolved transient absorption spectroscopy. The phenolic receptor molecule, bpy-phenol, binds to the F- ion through a hydrogen bond and senses the F- ion-via the Stokes-shifted CT band. Upon photoexcitation, CT from the phenol residue to the bpy residue promotes proton transfer from the phenol radical cation (ArOH center dot+) to the fluoride ion at ultrafast time scales of <150 fs (instrument response function limited) and 3 ps, separately. The fast and slow proton-transfer times are linked to two different types of hydrogen-bonding networks between the phenol residue and fluoride ion. Crystalline water in the fluoride salt hydrates mediates the proton-transfer reaction. This work demonstrates the participation of a hydrogen-bonded water bridge within a PCET reaction in a water restricted environment.

Proton-coupled electron-transfer processes in ultrafast time domain: evidence for effects of hydrogen-bond stabilization on photoinduced electron transfer - Dey, Ananta; Dana, Jayanta; Aute, Sunil; Maity, Partha; Das, Amitava; Ghosh, Hirendra N. (Chemistry-A European Journal, 2017)
The proton-coupled electron-transfer (PCET) reaction is investigated for a newly synthesized imidazoleanthraquinone biomimetic model with a photoactive RuIIpolypyridyl moiety that is covalently coupled to the imidazole fragment. Intramolecular H-bonding interactions between imidazole and anthraquinone moieties favor the PCET process; this can be correlated to an appreciable positive shift in the one-electron reduction potential of the coordinated anthraquinone moiety functionalized with the imidazole fragment. This can also be attributed to the low luminescence quantum yield of the RuII-polypyridyl complex used. The dynamics of the intramolecular electron-transfer (ET) and PCET processes are studied by using femtosecond transient absorption spectroscopy. The steady- state spectroscopic studies and the results of the time- resolved absorption studies confirm that H- bonded water molecules play a major role in both ET and PCET dynamics as a proton relay in the excited state. The electron- transfer process is followed by a change in the H- bonding equilibrium between AQ and imidazole in acetonitrile solvent, and protonation of AQ(-) water leads to PCET in the presence of water. A slower forward and backward electron- transfer rate is observed in the presence of D2O compared with that in H2O. These results provide further experimental support for a detailed understanding of the PCET process.